A case in support of implementing innovative bio-processes in the metal mining industry - Sánchez-Andrea, Irene (2016)
The metal mining industry faces many large challenges in future years, among which is the increasing need to process low-grade ores as accessible higher grade ores become depleted. This is against a backdrop of increasing global demands for base and precious metals, and rare earth elements. Typically about 99% of solid material hauled to, and ground at, the land surface currently ends up as waste (rock dumps and mineral tailings). Exposure of these to air and water frequently leads to the formation of acidic, metal-contaminated run-off waters, referred to as acid mine drainage, which constitutes a severe threat to the environment. Formation of acid drainage is a natural phenomenon involving various species of lithotrophic (literally rock-eating) bacteria and archaea, which oxidise reduced forms of iron and/or sulfur. However, other microorganisms that reduce inorganic sulfur compounds can essentially reverse this process. These microorganisms can be applied on industrial scale to precipitate metals from industrial mineral leachates and acid mine drainage streams, resulting in a net improvement in metal recovery, while minimising the amounts of leachable metals to the tailings storage dams. Here, we advocate that more extensive exploitation of microorganisms in metal mining operations could be an important way to green up the industry, reducing environmental risks and improving the efficiency and the economy of metal recovery.